Energetic proton acceleration by EMIC waves in Io’s footprint tail - Clark, G.; Szalay, J. R.; Sulaiman, A. H.; Saur, J.; Kollmann, P.; Mauk, B. H.; Paranicas, C.; Hue, V.; Greathouse, T.; Allegrini, F.; Glocer, A.; Garcia-Sage, K.; et al. (Frontiers in Astronomy and Space Sciences, 2023)
In this contribution, we present a survey of energetic proton observations associated with Io’s footprint tail (FPT) and compare their signatures with in-situ measurements of the plasma waves and lower-energy electron environment. We find further supporting evidence that proton acceleration in Io’s FPT is likely a consequence of wave-particle interactions via electromagnetic ion cyclotron waves that are generated by precipitating electrons into Jupiter’s ionosphere. This idea was originally proposed by (Clark et al., 2020; Sulaiman et al., 2020) based on NASA’s Juno mission likely transiting Io’s Main Alfvén Wing (MAW) during its twelfth orbit (i.e., PJ12). Additionally, the analysis of > 50 keV protons presented here highlights important observational details about the Io-Jupiter interaction, such as: 1) proton acceleration in Io’s FPT is a persistent feature and the energy flux carried by the protons are highest at smaller Io-Alfvén tail distances; 2) energetic protons exhibit positive correlations to both plasma waves and < 100 keV/Q electrons; 3) during a small number of Io FPT crossings, the protons display finer spatial/temporal structure reminiscent of the electron observations reported by Szalay et al. (2018); and 4) the proton pitch angle distributions are characterized by two types: conic distributions in, or near, Io’s MAW and isotropic, elsewhere.